Understanding college graduates' employability and its impact on employment and career outcomes: An empirical study to validate the Chinese Graduate Employability Scale (CGES) - Yu Dan (2022)
The employment difficulty of college graduates has been an issue of concern for Chinese universities and society for years, and a reliable measurement instrument for the concept of employability is needed. A longitudinal study was conducted to test the reliability and validity of the Chinese Graduate Employability Scale (CGES) and to examine the influence of college graduate employability on their post-graduation career development. Specifically, this study collected data in two time points respectively in 2019 (T1) and 2021 (T2) and tracked the sampled 2019 graduates’ employment outcomes and post-graduation career development. Exploratory factor analysis and confirmatory factor analysis were conducted on a sample (n=2,724) of 2019 fresh graduates from 17 universities across China to validate CGES and its three dimensions: “job-hunting skills””, “self-marketing skills” and “social skills”. The scale has high and stable convergent and discriminant validity and internal consistency reliability. Regression analysis shows that college students’ employability is positively associated with their satisfaction with employment outcomes upon graduation, and employability is positively related to their emotional intelligence. A longitudinal study (n=268) two years later (2021) shows that college students’ employability is positively related to their person-organization fit and career adaptability after graduation. These results demonstrate the criterion validity of the scale. Overall, the studies suggest that CGES is a reliable and valid measurement instrument for the scientific research of college graduate employability in China.